ENHANCING SUBJECTIVE WELL-BEING THROUGH GROUP COGNITIVE BEHAVIORAL THERAPY FOR WOMEN AFFECTED BY DOMESTIC VIOLENCE: EVIDENCE FROM A RANDOMIZED CONTROLLED TRIAL IN PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Domestic violence is a pervasive global public health issue with profound psychological consequences, particularly for women. Survivors often experience diminished subjective well-being (SWB), including low life satisfaction, heightened negative affect, and reduced positive affect. Despite the high prevalence of domestic violence in low- and middle-income countries like Pakistan, access to evidence-based psychological interventions remains limited. This study aimed to evaluate the effectiveness of Group Cognitive Behavioral Therapy (GCBT) in enhancing SWB among women survivors of domestic violence residing in a shelter home in Peshawar, Pakistan. A randomized controlled trial was conducted with 40 female participants, aged 18–50 years, who were randomly assigned to either an experimental group (n = 20) or a control group (n = 20). The experimental group received ten GCBT sessions over five weeks, while the control group received standard care. SWB was measured pre- and post-intervention using the ICP-Subjective Well-Being Scale, assessing positive affect, negative affect, and life satisfaction. Data were analyzed using independent samples t-tests. Participants in the GCBT group demonstrated a significant increase in positive affect (M = 52.84, SD = 10.9) compared to the control group (M = 36.90, SD = 13.4; t(38) = 4.05, p < .001). Negative affect significantly decreased in the experimental group (M = 16.40, SD = 6.31) relative to the control group (M = 27.05, SD = 12.9; t(38) = -3.20, p = .002). Although life satisfaction improved in the experimental group (M = 18.75, SD = 3.17), this difference did not reach statistical significance (p = .150). The findings indicate that GCBT is an effective and culturally appropriate intervention for improving SWB among women affected by domestic violence in Pakistan. Integrating GCBT into shelter home services and community-based programs could offer a cost-effective and scalable solution to address the psychological needs of this vulnerable population. Future studies with larger and more diverse samples are recommended to confirm these results and evaluate long-term outcomes.